Scoping review of six retrospective studies: risk factors associated with the case fatality rate of people infected with Coronavirus (COVID-19) - Adel Sadeq; Asim Ahmed Elnour; Farah Hamad Farah; Azza Ramadan; Judit Don; Ahmed Ibrahim Fathelrahman; Maisoun Alkaabi; Mohammed Baraka; Abubakar B Abubakar; Sasha Mohammed Elamin Suliman; Abdulla Al Amoodi; IsraaYousif Khidir; et al. (Wolters Kluwer Medknow Publications, 2022)
Background: It would be rational to describe the pattern of the clinical characteristics of the survivors and the nonsurvivors during the critical intensive-infection era of coronavirus disease 2019 (COVID-19). The explicit objective of the current scoping review was to delineate the predictive risk factors associated with case fatality rate (CFR). Methods: Six retrospective studies of subjects infected with COVID-19 published between December 1, 2020, and March 30, 2020, describing nonsurvivors in Wuhan/Hubei, China, were identified. Results: There were 1769 subjects with a mean age of 52 years, and 65.9% were male. The highest comorbidity reported was cardiovascular diseases at 22.2% (393/1769). The overall number of cases admitted to the intensive care unit was 228 (12.9%). The reported overall CFR was 7.7% (136/1769), with the highest at 28.2% (54/191), and the lowest at 1.4% (15/1099). The mean duration of onset until death for nonsurvivors was 15.3 days. Conclusion: We have found that older age, male gender, the longer duration from onset till death (days), development of acute respiratory distress syndrome/shock, preexisting diabetes, and preexisting cardiovascular diseases were the major risk factors associated with high CFR.